Case Report: Spectrum of interesting ocular manifestations following COVID-19 vaccination: a case series of real-world presentations - Tajunisah, Iqbal; Tan, Shao Sze; Effendi-Tenang, Irina; Samsudin, Amir; Ling, Kiet-Phang; Tan, Wee Yong; Ramasamy, Sunder; Fong, Kenneth Choong Sian (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose We report the ocular findings that patients experienced after receiving the coronavirus disease 2019 (COVID-19) vaccination in three different eye centers in Malaysia. Observations A total of four cases were reported. Three patients received the Pfizer-BioNTech vaccine, while the other received the Oxford AstraZeneca type. Ocular symptoms occurred after the first vaccine dose in two patients and after the second vaccine dose in the other two. Three out of four patients required active treatment for their vision complications postvaccination. The first patient had acute-onset retinal pigment epitheliitis within 3 h of vaccination and was treated conservatively. The second patient developed unilateral choroidal neovascularization 3 days after vaccination and required intravitreal antivascular endothelial growth factor injection. The third patient presented with bilateral acute multifocal placoid pigment epitheliopathy a week after vaccination and responded to intravenous methylprednisolone. The fourth patient presented with herpes zoster infection and unilateral anterior nongranulomatous uveitis 2 weeks after vaccination and was treated with oral acyclovir and topical corticosteroids. All patients reported some amount of visual recovery. Conclusions and importance Visual symptoms and various ocular adverse events can occur following COVID-19 vaccination, which warrants further investigation and urgent intervention if necessary. We would suggest patients receiving the COVID-19 vaccination be aware of possible ocular complications and report any symptoms, regardless of severity.